Anecdata: children’s and adults’ evaluation of anecdotal and statistical evidence - Nissel, Jenny; Woolley, Jacqueline D. (Frontiers in Developmental Psychology, 2024)
Pseudoscientific beliefs, including vaccine-related and other types of conspiracy theories, are often formed through reliance on personal anecdotes shared by people with similar belief sets. In the present study, we explore one aspect of pseudoscientific versus scientific reasoning by studying the development of the use of anecdotal versus statistical evidence. To do so, we asked 7-and 10-yearolds and adults to help an agent solve a problem by choosing one of two potential solutions, one supported by an anecdote and one by a graph. Results revealed significant age differences, with older participants more likely to value the graphical over the anecdotal evidence. Participants who chose the anecdotal solution frequently justified their choices by referring either to an inferred causal relationship between the chosen solution and the outcome or to characteristics of the person who provided the anecdote. Participants who chose the graphical solution frequently referred to quantity. Our findings suggest that both a greater valuation of statistical information and an increased ability to reflect critically about causal relationships may be critical in resisting the persuasive power of anecdotes, and hence, making valid evidence-based decisions.